2015
DOI: 10.1002/jmor.20484
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and ultrastructure of the somatic cells in Astacus leptodactylus ovary

Abstract: We defined the somatic environment in which female germinal cells develop, and performed ultrastructural analyses of various somatic cell types, with particular reference to muscle cells and follicle cells, that reside within the ovary at different stages of oogenesis. Our findings show that ovarian wall of the crayfish is composed of long muscle cells, blood cells, blood vessels and hemal sinuses. The follicle and germinal cells lie within a common compartment of ovarian follicles that is defined by a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The interstitial compartment situated between the inner muscular layer of ovarian wall and the basal matrix of ovarian follicle compartment contains muscle cells, hemal sinuses, blood vessels, and blood cells. Ultrastructure of the A. leptodactylus ovary has been described recently by our group (Petrescu et al, 2016).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The interstitial compartment situated between the inner muscular layer of ovarian wall and the basal matrix of ovarian follicle compartment contains muscle cells, hemal sinuses, blood vessels, and blood cells. Ultrastructure of the A. leptodactylus ovary has been described recently by our group (Petrescu et al, 2016).…”
Section: Resultsmentioning
confidence: 86%
“…Intracisternal granules are considered to be the sites of the endogenous precursors of proteinaceous yolk (Beams & Kessel, 1963). Previous studies have shown the presence of coated vesicles in previtellogenic oocytes of A. leptodactylus , suggesting that, before the onset of vitellogenesis, follicle cells can deliver other substance into oocytes by receptor-mediated endocytosis (Petrescu et al, 2016). In light of the findings in our study, we can therefore reasonably speculate that nickel may bind to various ligands in hemolymph or follicle cells and in this form is incorporated through endocytosis in the yolk.
Figure 6 Autometallographic staining of oocytes from nickel-exposed Astacus leptodactylus .
…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the cortical cytoplasm of previtellogenic and vitellogenic oocytes of Astacus leptodactylus were characterized by the presence of coated vesicles. [ 39 ] The authors suggested that before the onset of vitellogenesis, follicle cells can deliver other substances into oocytes by receptor-mediated endocytosis. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] The authors suggested that before the onset of vitellogenesis, follicle cells can deliver other substances into oocytes by receptor-mediated endocytosis. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%